Queering the Global Filipina Body : Contested Nationalisms in the Filipina/o Diaspora - Velasco, Gina K., 1977- (Book collections on Project MUSE., 2020)
"This project examines the gendered and sexual politics of representing the transnational Filipina body produced within Filipina/o American culture, yet situated in a Philippine economy that relies on overseas Filipina/o migrant labors. Considering how the "transnational Filipina body" refers to gendered figures of Filipina/o transnationalism that includes maids, nannies, nurses, and sex workers, Gina Velasco examines how these bodies circulate within both Filipina diasporic cultural production as well as global popular culture. In order to present a queer analysis of Filipina/o American cultural production, the author analyzes several figures of Filipina/o transnationalism: the mail order bride, the sex worker and trafficked woman, the Filipina/o American expatriate, and the cyborg as a utopian figure of transnational belonging. Identifying these bodies in Filipina/o American performance, video/film, websites, and heritage language programs, Velasco considers whether Filipina/o American tropes of the Philippine nation, which both reproduce and challenge the heteronormativity and masculinism of nationalism, can encompass a queer and feminist imagining of the Filipino labor diaspora"--